Riding the leadership rollercoaster : an observer's guide - Kets de Vries, Manfred F. R. (Palgrave Macmillan, 2017)
A collection of short, bite-sized nuggets of insight into the psychological ups and downs of the leadership journey, this book provides leaders and their coaches with the insights that can help them take some control of the ride. -- Edited summary from book.
Keywords: Leadership -- Psychological aspects.; Success in business.; Management science.; elektronické knihy; electronic books